2011
DOI: 10.3389/fnmol.2011.00023
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective actions of ghrelin and growth hormone secretagogues

Abstract: The brain incorporates and coordinates information based on the hormonal environment, receiving information from peripheral tissues through the circulation. Although it was initially thought that hormones only acted on the hypothalamus to perform endocrine functions, it is now known that they in fact exert diverse actions on many different brain regions including the hypothalamus. Ghrelin is a gastric hormone that stimulates growth hormone secretion and food intake to regulate energy homeostasis and body weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 142 publications
(191 reference statements)
0
41
0
Order By: Relevance
“…Little is known about the role of obestatin in cognition, as opposed to ghrelin where there is more information available (Frago et al 2011). Experimental studies in rats have demonstrated the neuroprotective role of ghrelin (Carlini et al 2002(Carlini et al , 2004, as well as of obestatin (Carlini et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the role of obestatin in cognition, as opposed to ghrelin where there is more information available (Frago et al 2011). Experimental studies in rats have demonstrated the neuroprotective role of ghrelin (Carlini et al 2002(Carlini et al , 2004, as well as of obestatin (Carlini et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin and ghrelin receptor agonists have shown marked neuroprotective effects in rodent models and cell culture models of excitotoxicity, epilepsy, stroke (with reperfusion), Parkinson's disease, Alzheimer's disease, and encephalomyelitis [15,11,54,55]. Ghrelin administration also alleviates diabetic neuropathy in rodents [56,57].…”
Section: Ghrelin's Role In Cognition and Neuroprotectionmentioning
confidence: 97%
“…This is a seven-pass G protein-coupled receptor, expressed not only in the pituitary, but also the hypothalamus, hippocampus, and other regions of the brain, as well as in a high proportion of the body's tissues; hence, ghrelin can exert a wide range of physiological effects. Des-acyl ghrelin (ghrelin lacking an octanoate substituent) also circulates in plasma, but fails to activate GHS-R1a; it may however interact with other receptors not yet characterized [15,16].…”
Section: Physiological Role Of Ghrelinmentioning
confidence: 98%
“…Release of GH from the anterior pituitary can be stimulated by ghrelin, as well as by its analogues the GH secretagogues (GHSs), which include GH-releasing peptides (GHRP)-1, -2 and -6. Both ghrelin and GHSs bind to GHS receptors not only expressed in the pituitary but also widely distributed in the CNS (Ghigo et al 2001, Zigman et al 2006, Frago et al 2011. Upon binding to the GHS receptor, which has been renamed ghrelin receptor (GRLN-R1a; Davenport et al 2005), GHSs activate pathways that regulate the activation of downstream MAPK, protein kinase B (PKB/Akt), nitric oxide synthase and adenosine monophosphate-activated protein kinase cascades in different cellular systems (Petersenn 2002).…”
Section: Introductionmentioning
confidence: 99%